COMMUNICATION STRATEGY IN DELIVERING DA'WAH MESSAGES AND INCREASING THE NUMBER OF FOLLOWERS - Dadi Nurjaman; Van Riswansyah Zebua (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2022)
This study aims to describe how the communication strategy of an Instagram account @kajianislam is in conveying da'wah messages and in increasing its followers. This descriptive research was carried out in 2022 by selecting the object of study on the social media Instagram account @kajianislam using qualitative research methods. The results of this study indicate that the Instagram account @kajianislam is viewed from a communication strategy according to Onong Uchjana Effendy, namely identifying communication goals, selecting communication media, assessing communication objectives and source credibility. He also took steps to increase his followers so that he was successfully followed by 2.8 million followers.